The Existence of Halaqah as a Center of Islamic Educational Scholarship in Minangkabau - Mukhtar, Dertha; Iswantir, Iswantir; Susanti, Riri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This articel discusses the existence of halaqah as a center of Islamic scholarship in Minangkabau, examining its historical background, institutional characteristics, socio-cultural functions, and the dynamics of its transformation toward modern forms of Islamic education. The study employs a literature review method by analyzing journal articles, conference proceedings, and historical studies related to surau, halaqah, and the Minangkabau network of scholars (ulama). The findings indicate that halaqah often manifested in the form of surau institutions or pondok networks served as the main foundation for the transmission of Islamic knowledge, the formation of scholars, and the internalization of local (customary) values oriented toward Sharia. However, since the 20th century, these scholarly institutions have undergone processes of modernization and pluralization.